Modeling the pattern of energy consumption in residential buildings based on optimal energy management approach (A case study: Conventional Apartments in Lahijan, Iran) - Armin Golshahi; Vahid Ghobadian; Mehrdad Matin (Anthropogenic Pollution)
Nowadays, buildings are one of the most consuming sectors that cause excessive energy loss. The present applied research aimed to model the energy consumption pattern in conventional residential apartments in Lahijan city (Gilan province, Iran). Design Builder software was used to model four scenarios, including the current state, the use of a movable canopy, the use of photovoltaic panels, and the combined state. According to the results, the infiltration load coefficient was obtained to be 1778 W/K. The highest heat dissipation in cold seasons was related to the roof and glazing parts. The lighting state was within the standard range in 12%, more than the standard in 52% and less than the standard in 36% of the points. The shortcomings of the study buildings were significant from the energy point of view, so that the average heat transfer coefficients of the walls, windows and ceilings were 2.5, 1.7 and 2.2 times the standard value of Standard Topic 19 of the National Building Regulations, respectively. The total electricity consumption was 776,543 kilowatt-hours per year (kWh/year), and the panels were able to generate 14.87% of the required electricity (115,544 kWh/year). The use of smart movable canopy and photovoltaic panel led to energy savings of 18% and 17%, respectively. The simultaneous use of both would bring the amount of energy saving by 24%. To conclude, adopting purposeful and effective measures and training can lead to saving energy consumption and benefiting from clean energy in such buildings.